2012
DOI: 10.1186/1758-5996-4-15
|View full text |Cite
|
Sign up to set email alerts
|

The skin function: a factor of anti-metabolic syndrome

Abstract: The body’s total antioxidant capacity represents a sum of the antioxidant capacity of various tissues/organs. A decrease in the body’s antioxidant capacity may induce oxidative stress and subsequent metabolic syndrome, a clustering of risk factors for type 2 diabetes and cardiovascular disease. The skin, the largest organ of the body, is one of the major components of the body’s total antioxidant defense system, primarily through its xenobiotic/drug biotransformation system, reactive oxygen species-scavenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 112 publications
(177 reference statements)
0
50
0
4
Order By: Relevance
“…In addition, it should be considered that a disorder in the elimination of reactive oxygen species (ROS) can result in an increased level of circulating lipids and cholesterol in the blood which increases the risk of dyslipidemia and MS (29,30). Based on the results of this research, an increased level of ROS and lipid peroxidation in LP was observed, which enhanced the inflammatory response by immunological mechanism and increased the serum level of nitric oxide, malondialdehyde, and superoxide dismutase (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, it should be considered that a disorder in the elimination of reactive oxygen species (ROS) can result in an increased level of circulating lipids and cholesterol in the blood which increases the risk of dyslipidemia and MS (29,30). Based on the results of this research, an increased level of ROS and lipid peroxidation in LP was observed, which enhanced the inflammatory response by immunological mechanism and increased the serum level of nitric oxide, malondialdehyde, and superoxide dismutase (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 79%
“…It has been proposed that any derangement in the elimination of ROS through sebum will increase levels of circulating lipids and cholesterol, thus increasing the risk of dyslipidemia and Metabolic syndrome. 9,11 The proposed immunological defect in endocrine dysfunction causing diabetes mellitus may also contribute to development of lichen planus.…”
Section: Introductionmentioning
confidence: 99%
“…15 Vitiligonun patogenezinde yer alan serbest oksijen radikallerinin metabolik olaylar ile de ilişkili olabileceği dü-şünülmüştür. 16 Obez insanların adipoz dokusunda melanogenezisin artması bu durumu desteklemektedir. 17 İnflamatuar süreçte doğal immün sistem tarafından salınan bazı endojen antiinflamatuar mediyatörlerin proinflamatuar ve antiinflamatuar faktörler arasındaki dengeyi sağlayarak inflamasyonu kontrol edebildiği bildirilmektedir.…”
Section: Discussionunclassified